Pengaruh Keterpaparan Media Informasi Mengenai Kesehatan Reproduksi Terhadap Perilaku Seksual Remaja - Nadirahilah Nadirahilah (Jurnal Persada Husada Indonesia, 2017)
Accessibility to reproductive health information is getting more easy through print and electronic medias. This can be influential towards adolescents sexual behavior especially undergraduates. This study aims to find out media influence towards undergrads sexual behavior. Study population samples were 156 STIKes Jayakarta undergrads. The study showed 147 respondents (94.2%) uses the internet media to access information on reproductive health and respondents with sexual behavior risks of kissing at 62 students (39.7%), foreplay at 30 students (19.2%) and 6 students (3.8%) engaging in sexual activity. The print and electronic medias influence towards STIKes Jayakarta students sexual behavior showed a statistic significant (p value < 0.05). With more students being exposed to electronic media liked the internet and the television to access information on reproductive health, the risks of sexual behavior occurrence can be minimalized.